The Effect of Digital Marketing Literacy and Digital Marketing Strategy on Customer Satisfaction and Its Implications for Customer Loyalty. - Fathorrahman, Fathorrahman; Wahyuni, Ummy; Zainurrafiqi, Zainurrafiqi (Al-Amien Prenduan for Islamic Institute, 2025)
This study aims to analyze the influence of digital marketing literacy and strategies on beauty products in Pamekasan Regency. The sample used in this study involved 190 beauty product consumers. A quantitative approach was applied using the Partial Least Square - Structural Equation Modeling (PLS-SEM) analysis method. This study found that digital marketing literacy and digital marketing strategies have a positive and significant influence on consumer satisfaction and loyalty. Furthermore, consumer satisfaction has also been shown to increase their loyalty. These findings enrich the digital marketing literature by highlighting the important role of effective literacy and strategies in building consumer satisfaction and loyalty. Practically, these results can serve as a foundation for designing more effective digital marketing strategies and provide guidance for companies in the beauty industry to strengthen relationships with consumers through more optimal digital marketing.